PENDIDIKAN KARAKTER DALAM PENDIDIKAN ISLAM - Ibrahim Sirait (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2022)
Education has a very important role. This is in accordance with Law no. 20 of 2003 concerning the National Education System Article 3 of the Law states that national education functions to develop capabilities and shape the character and civilization of a nation with dignity in the context of the intellectual life of the nation. So for the development of the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. Education in Indonesia today seems to be in decline. This is also proven by the many cases of brawls between schools, universities, state officials or even from the apparatus themselves, the cause of all of this could be due to a lack of exemplary from a teacher, lack of embedded morals and values. Islam in the hearts of students, resulting in a character crisis